PENDIDIKAN VOKASI SEBAGAI PONDASI BANGSA MENGHADAPI GLOBALISASI - Kuntang Winangun (Universitas Sarjanawiyata Tamansiswa, 2017)
One indicator of the era of globalization is characterized by the emergence of free trade, free goods out of the country knows no bounds (borderless), this indication shows that the workforce with professional qualifications are highly demanded in the world of work in this era of globalization.In the organization of education systems-oriented world of work in Indonesia, there are two terms used education, namely: vocational education and vocational education. In Article 15 of Law No. 20 of 2003 on National Education System explained vocational education is secondary education that prepares students primarily for work in a particular field, while vocational education is higher education that prepares students to have a job with a certain applied skills equivalent to the maximum degree program. Thus, vocational education is provision of formal education which was held in higher education, such as: polytechnic, diploma, or the like which are directly related to the advancement of knowledge and skills necessary for candidates for employment in the field of engineering and industrial services. Vocational education building 8 Competency, namely: Communication Skills, Critical and Creative Thinking, Information/ Digital Literacy, Inquiry/ Reasoning Skills, Interpersonal Skills, Multicultural/ Multilingual Literacy, Problem Solving, Technological Skills.With vocational education effective and efficient is expected to generate prospective workers who have the soft skills and hard skills with critical thinking ability and skill in solving problems to face the world of work in the era of globalization.